The Cartesian Set Theory: A Unifying Theory for Mental Disorders - Bucci, Andrea (Journal of NeuroPhilosophy, 2023)
In this essay I want to propose a relative new theory about conscious states, human experience and its application in the study of mental disorders in the broader sense. I will call this theory, which has some similarities with the most famous Cartesian Theatre metaphor by Daniel Dennet, The Cartesian Set Theory. My Cartesian Set Theory try to reveal with the help of some analogies the entire field of human experience and, I retain obvious, the conscious one. Contextually, I will try to explain how the phenomenological inquiry overlap the biological studies about the brain functioning in psychiatric disorders. Immediately after, I will show how The Cartesian Set Theory can give a unifying vision of mental disorder, boundaries experience, and to predict new disorders.